(2x-7)(6x+3)=0

Simple and best practice solution for (2x-7)(6x+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-7)(6x+3)=0 equation:



(2x-7)(6x+3)=0
We multiply parentheses ..
(+12x^2+6x-42x-21)=0
We get rid of parentheses
12x^2+6x-42x-21=0
We add all the numbers together, and all the variables
12x^2-36x-21=0
a = 12; b = -36; c = -21;
Δ = b2-4ac
Δ = -362-4·12·(-21)
Δ = 2304
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{2304}=48$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-36)-48}{2*12}=\frac{-12}{24} =-1/2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-36)+48}{2*12}=\frac{84}{24} =3+1/2 $

See similar equations:

| 17+n=-3+n+21-5n | | 5x+2x+3x10x=180 | | 7c+20=6 | | 3y+64=180 | | 12x+48=3x+72 | | 1/2(4x+6)=5x+18 | | 10+4x=7x+4-x | | 1=x/2=6 | | 3y+1+63=180 | | 2x+6-10x=30* | | Z+5+3y+1=180 | | E^9x+3=3 | | 3y+1+78=180 | | 7c-20=6 | | -8=x-24 | | 2/5x-3=12 | | -8b+6+6b=-3b+11+6 | | 48y+48y=5y-18 | | 100+x+25=180 | | -23=17+4y | | (3z+6)=4z | | 5x+14=35+3x | | 1/4(12x+16)+2=18 | | x3-12=-15 | | y/3+12=7 | | 25+2=3x-5 | | -13k+6=-12k | | -4+8+2x*4=x+47 | | 6x+8=2(16-x) | | 3x2=-300 | | 20+18s=-8+20s | | 3a-(6a-5)=26 |

Equations solver categories